Experimental Investigation on Influencing Factors of Rock Fragmentation Induced by Carbon Dioxide Phase Transition Fracturing - Bo Gao; Youjiang Yang; Weilong Xue; Anhui Guo; Xuedong Luo (Shock and Vibration)
Carbon dioxide phase transition fracturing is a novel physical blasting technique, which is gradually used in mining and underground space engineering. The improvement of its rock breaking efficiency is the key concern in the application. In this paper, field experiments of CO2 phase transition fracturing were conducted. Based on the strain monitoring and fracturing crater volume measuring, the variation of CO2 filling amount and shear sheet thickness on rock fragmentation of CO2 phase transition fracturing was investigated. The experimental results indicated that the fracturing crater is shaped as an elliptical cone that is longer in the jet direction and shorter in the vertical jet direction. With the increase of the CO2 filling amount, the excavated crater volume gradually increases, but the growth rate gradually decreases. The powder factor is constant within a certain charge amount, and after exceeding this charge amount, the powder factor of CO2 increases significantly. As the shear sheet thickness increases, although the consultant peak stress gradually increases, its growth rate is still unchanged. The crater volume and its growth rate gradually increase in the same situation. Moreover, with the shear sheet thickness increase, the CO2 powder factor decreases continuously, and the decline rate remains unchanged.